An Analysis of Ideology and Translation Quality on Bilingual text “NANDA” English into Indonesian - Maryani Maryani (STKIP PGRI Lubuklinggau, 2019)
An Analysis of Ideology and Translation Quality on Bilingual text “NANDA” English into Indonesian Maryani Institute of Health Science Surya Global Yogyakarta marry.tenang@gmail.com Abstract Some facts indicate that the majority of nursing and medical books used in universities in Indonesia still written in a foreign language (English), but the nursing and medical students are still less able to read the English books. Therefore, this situation makes a translator of English source book into Indonesian needed in the academic community. This research is aimed to explain the ideologies and to assess the quality of accuracy, acceptability and rediability of the translation on the target text ‘NANDA’. This research was a descriptive qualitative research. The design was embedded case study focusing on a single case. Technique of collecting data was content analysis, reading technique and noting technique. The data were analyzed using equivalent method. The results of research show that the foregnization ideology tended to be used in this book. Then, the impact of the application of those translation techniques toward the quality of acceptability of the translation was good than others. The acceptable category got the first rank than accuracy and readibility, because the data found in this research were natural, smooth and flexible. It does not look like translation. Keywords : translation, ideology, acceptability, accuracy, readibility level.